(untitled) (Research, Society and Development, 2020)
The craft beer market is booming and, in this scenario, Brazil presents itself as one of the most innovative countries in the segment. Volatile organic compounds are present in craft beers as being largely responsible for the aroma and flavor of the product and, therefore, their determination is essential both for analysis of the final product and during the control of the production process. Thus, this work aimed to optimize an analytical method for quantification of volatile compounds in craft beers, using gas chromatography with headspace sampling. The study involved sample decarbonation tests analyzing different agitation times and optimization of the sampling conditions that employed a factorial design 23, considering the factors temperature, heating time of the headspace oven and sample injection volume. The acetaldehyde, ethyl acetate, n-propanol, isobutanol and isoamyl alcohol analytes had their detection and quantification limits calculated and were determined in American Lager, Dunkel, Helles, IPA, Ale, Wit, Weiss and Dobbel craft beers. Multivariate analysis was performed using Principal Component and Hierarchical Cluster Analysis and the influence of higher alcohols on sample separation was observed. The method proved to be suitable for quantification of volatiles in the craft beers and can be used both in the analysis of the final product, and during the formation of these compounds during the fermentation process.